Calcium dysregulation in relation to Alzheimer‐type pathology in the ageing brain. Issue 7 (29th October 2013) - Garwood, C.; Faizullabhoy, A.; Wharton, S. B.; Ince, P. G.; Heath, P. R.; Shaw, P. J.; Baxter, L.; Gelsthorpe, C.; Forster, G.; Matthews, F. E.; Brayne, C.; Simpson, J. E.; et al.
Abstract : Aims: Calcium dyshomeostasis is implicated in the pathogenesis of several neurodegenerative disorders including Alzheimer's disease. However, much of the previous research has focused on changes in neuronal calcium signalling. In a recent microarray study we identified dysregulation of several key signalling pathways including the Ca 2+ signalling pathway in astrocytes as Alzheimer‐type pathology developed. In this study we sought to determine the expression of calpain‐10 and calcium/calmodulin‐dependent kinase alpha (CamKIIα) in relation to Alzheimer‐type pathology in a population‐based study. Methods: Using post mortem temporal cortex samples derived from the Medical Research Council Cognitive Function and Ageing Study (MRC‐CFAS) ageing brain cohort we examined calpain‐10 and CamKIIα gene and protein expression using quantitative polymerase chain reaction and immunohistochemistry. Results: We demonstrate that astrocytic expression of calpain‐10 is up‐regulated, and CamKIIα down‐regulated with increasing Braak stage. Using immunohistochemistry we confirm protein expression of calpain‐10 in astrocytes throughout the temporal cortex and demonstrate that calpain‐10 immunoreactivity is correlated with both local and global measures of Alzheimer‐type pathology. In addition, we identify a subpopulation of calpain‐10 immunoreactive interlaminar astrocytes that extend processes deep into the cortex. CamKIIα is predominantly neuronal in localization and is associated with the presence of diffuse plaques in the ageing brain. Discussion: Dysregulated expression of key calcium signalling molecules occurs with progression of Alzheimer‐type pathology in the ageing brain, highlighting the need for further functional studies of astrocytic calcium signalling with respect to disease progression.